Independência do judiciário: mensurando o viés político das cortes brasileiras - Lopes, Felipe de Mendonça (2013)
The degree of political influence to which the judiciary is subject has broad implications on economic development. For the executive’s non-expropriation commitment to be credible, it is necessary that the judiciary should be free to impartially mediate disputes between the State and its citizens. If there is too much political influence in the judiciary, the credibility of such commitment is tainted, which discourages private investment, thus hampering economic growth. In Brazil, an institutional peculiarity allows us to do a comparison that is unprecedented in the literature. As there are two courts, the Supremo Tribunal Federal (STF) and the Superior Tribunal de Justiça (STJ), which deal with similar matters and have different restrictions on the appointment of its members, it is possible to compare the degree of political influence to which they are subject. Thus, we propose to test: 1 - if there is a political appointment effect on the decisions of the justices of the two courts, 2 - if there are differences on the degree of political influence in accordance to the restrictions on presidential nomination in place in each court; 3 - if the justices of both courts make strategic use of their positions, that is, actively benefit the party that has appointed them. We find evidence of the second and, partially, of the third effect.